2022
DOI: 10.1007/s00442-022-05138-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning and acoustic predation tags to classify migration fate of Atlantic salmon smolts

Abstract: Mortality and predation of tagged shes presents a serious challenge to interpreting results of acoustic telemetry studies. There is a need for standardized methods to identify predated individuals and reduce the impacts of "predation bias" on results and conclusions. Here, we use emerging approaches in machine learning and acoustic tag technology to classify out-migrating Atlantic salmon (Salmo salar) smolts into different fate categories. We compared three methods of fate classi cation; predation tag pH senso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Consequently, these factors could lead to modifications in fish physiological and behavioral parameters, significantly affecting the overall health, particularly in early-life fish populations. Additionally, predatory species relying on speed for prey capture may experience reduced success rates and hindered growth, whereas for migrating species, changes in swimming performance could lead to delays or reductions in migration success (Notte et al, 2022).…”
Section: Tagging Effects On Fish Behavior and Recovery Timementioning
confidence: 99%
“…Consequently, these factors could lead to modifications in fish physiological and behavioral parameters, significantly affecting the overall health, particularly in early-life fish populations. Additionally, predatory species relying on speed for prey capture may experience reduced success rates and hindered growth, whereas for migrating species, changes in swimming performance could lead to delays or reductions in migration success (Notte et al, 2022).…”
Section: Tagging Effects On Fish Behavior and Recovery Timementioning
confidence: 99%
“…These transmitters have a unique sensor that triggers a change in tag transmission as predator digestive enzymes break down a polymer coating (Halfyard et al 2017). Most tests of this technology to date have occurred in laboratory or captive settings (Halfyard et al 2017;Lennox et al 2021), but more recent research has implemented these transmitters in the wild (Klinard et al 2019;Weinz et al 2020;Notte et al 2022). Weinz et al (2020) observed predation triggers on 32% of tagged Yellow Perch Perca flavescens and changes in movement patterns of tagged fish aligned with transmitter-identified predation events.…”
Section: Introductionmentioning
confidence: 99%